Singend is die geloof in sy element ... Gemeentesang as kommunikatiewe handeling - E. C. Kloppers (Acta Theologica)
In the worship service the faith is communicated on various levels by means of symbolic language and actions. Departing from the theory of communicative actions, it is shown that communicative actions are ways of communicating symbolically, by being part, taking part, and becoming part of an action. In this article it is argued that in many ways music has the qualities of a symbolic or metaphorical language. Singing and making music in the church service are therefore also communicative actions through which the experience of faith is expressed and communicated with others. Communicating the faith through music is determined by the work of the Holy Spirit — singing is a pneumatic act.